Analisis Keefektifan Kalimat pada Artikel dalam Website Kompasiana.com Edisi Desember 2024 tentang Kesehatan Mental sebagai Sumber Belajar Siswa SMP Kelas VII - Sailur Rohmah; Nova Salwa Qurrotul ‘Aini; Adhelia Citra Dewi; Agus Hakam Asathinuzzaman; Faiq Fairus Ashari; Muhammad Novan Maulana; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
Learning resources refer to anything that contains information to be presented either through media or for self-learning. This study aims to provide readers, especially seventh-grade junior high school students, with an understanding of which sentences are effective and which ones still need improvement in an article about mental health on the Kompasiana.com website, December 2024 edition. The research approach used in this study is descriptive qualitative. The data collection techniques used are the listening technique to gather data by listening to the language usage, followed by the note-taking technique to record words or sentences for analysis. Data presentation is done informally. The results of the analysis show that the most common error type is the inefficiency of word usage, with 12 sentences that are redundant and overly wordy. The second most common error is the use of overly simple sentences, with 7 sentences. The third error type is the use of foreign language, found in 3 sentences. The next error type is mismatched information, found in 2 sentences, and the last is errors in sentence structure, found in 1 sentence. This study is expected to help students understand how to construct more effective sentences.